Peran Mediasi Kepuasan pada Pengaruh Komukasi Internal dan Perilaku Menyimpang Terhadap Kinerja Pegawai - Nur Djannah Kottahatuhaha; Conchita Valentina Latupapua; Agusthina Risambessy (Univiversitas Dr. Djar Wattiheluw, 2023)
The purpose of this research is to examine and analyze the effect of internal communication and workplace deviant behaviour on employee performance through direct and indirect job satisfaction. The research was conducted on Self- Help Housing Stimulant Assistance (BSPS) activities at the Housing and Settlement Area Office of Central Maluku Regency. The type of data used is quantitative data. Data was collected through a questionnaire to 47 respondents. The data analysis technique uses statistical analysis using the outer model analysis test, inner model analysis test, and hypothesis testing. Data processing using SmartPLS 3. The results showed that: (1) internal communication has no direct effect on employee performance, (2) direct internal communication has a positive and significant effect on job satisfaction, (3) workplace deviant behavior has a negative and significant effect on job satisfaction directly, (4) workplace deviant behavior has a negative and significant effect on employee performance, (5) job satisfaction has a positive and significant effect on employee performance, (6) job satisfaction is a mediating variable for the indirect effect of internal communication on employee performance, and (7) job satisfaction is a variable mediating the indirect effect of workplace deviant behavior on employee performance.